The Power of Unrequited Love: The Parasocial Relationship, Trust, and Organizational Identification Between Middle-Level Managers and CEOs - Liao, Youliang; Lin, Bin; Zhou, Haiyan; Yang, Xi (Frontiers in Psychology, 2021)
Parasocial relationship(PSR) originated from fans' one-sided feelings to celebrity or superstars. PSR is a one-sided and virtual relationship emerging when individuals are not able to obtain normal social interaction with the specific person. The relationship between CEOs and the public is also parasocial. Due to the rapid expansion of firms, the PSR between employees and CEOs is ubiquitous. CEOs and middle managers are key components of a firm and are crucial to firm strategies and control systems. Middle managers play an important role in information transmission. In organizational hierarchy, CEOs affect low-level employees through middle managers. Prior studies found that CEOs manage subordinates by traditional approaches including leadership, management practices, resource allocation, and organizational culture. In this study, we investigate how parasocial relationship between the middles and CEOs affects the organizational trust and then the organizational identification of middles. We find that the PSR between middle managers and CEOs has a positive effect on the organizational identification of middle managers, which is mediated by the organizational trust of middle managers. Our paper contributes to parasocial Interaction theory, trust theory, and social identity theory. Practical implications for the internal relationship management, corporate governance and performance management are discussed.